2020
DOI: 10.1177/0194599820921392
|View full text |Cite
|
Sign up to set email alerts
|

Palatine Tonsilloliths and Actinomyces: A Multi‐institutional Study of Adult Patients Undergoing Tonsillectomy

Abstract: Objective To better characterize associations between Actinomyces and tonsillolith versus nontonsillolith tonsillectomy specimens. Study Design Bi-institutional retrospective case-case study. Setting University and county hospital. Subjects and Methods Adult patients with a clinical history of tonsilloliths who underwent tonsillectomy from January 2006 to December 2018 were included. Patients undergoing tonsillectomy for tonsillar hypertrophy and chronic tonsillitis were identified as comparative cases. Simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(113 reference statements)
0
5
0
Order By: Relevance
“…In our study, Actinomyces was found in 31.4% of patients. In the literature, the prevalence of Actinomyces colonies in palatine tonsils removed due to recurrent tonsilitis and OSAS ranges from 0.8% to 61.6% [2,14,16,[29][30][31][32]. In their study on a large cohort of patients, Aydin et al found that this percentage was 6.7% for the entire study population, including children (n = 1252) and adults (n = 568) [31].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In our study, Actinomyces was found in 31.4% of patients. In the literature, the prevalence of Actinomyces colonies in palatine tonsils removed due to recurrent tonsilitis and OSAS ranges from 0.8% to 61.6% [2,14,16,[29][30][31][32]. In their study on a large cohort of patients, Aydin et al found that this percentage was 6.7% for the entire study population, including children (n = 1252) and adults (n = 568) [31].…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, they questioned whether Actinomyces played an important role in the pathogenesis of this condition. They also reported that Actinomyces-targeted treatment of tonsilloliths failed to be effective [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the bacteria as a foreign nidus are periodontal disease-related bacteria, such as Actinomyces, Eubacterium, Fusobacterium, Megasphaera, Porphyromonas, Prevotella, Selenomonas, and Tannerella spp. [ 16 , 17 ]. Oral bacteria in secretions in contact with tonsillar epithelium may adhere to the mucosal surface and may stimulate cytokine production by mucosal epithelium [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cooper et al [2] reported that Actinomyces is a common resident of an abnormal tonsil and forms a nidus for calcification. However, a recent study reported that while a strong association was identified between Actinomyces and tonsilloliths, this pathological calcification is not based on solely one microorganism because of its polymicrobial nature [6]. A limited number of studies, investigating the bacterial composition of tonsilloliths, focused on heterogeneous microbial composition [7, 8].…”
Section: Introductionmentioning
confidence: 99%